Container Constructions in Yudja: locatives, individuation and measure - Suzi Lima (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
The possible interpretations of container phrases (such as ‘cups of sugar’) has been long debated in the formal semantics literature because container phrases can be associated with a variety of possible readings that go from individuation to measure. In this paper we explore the interpretation of container phrases in Yudja (Tupi stock, Brazil), a language where container phrases are optional in construction with numerals and are morphosyntactically identical to locative phrases. Based on experimental studies with Yudja children and adults we intend to show that these expressions are ambiguous in at least three ways (locative, individuation and measure) and that a locative reading might emerge even in scenarios where the verb and the context favor a measure interpretation. Furthermore, this paper provides evidence that there is no hidden container phrase when numerals are combined with notional mass nouns and that, supporting Partee and Borschev (2012), the results of the studies show that, indeed, the individuation reading is more “primitive”, i.e. it precedes measuring in language acquisition.
Keywords: container phrases; measuring; individuation; concrete portions